The Correlation of Sleep Quality and Cognitive Function In Students Of the Faculty Medicine during the Covid-19 Pandemic - Clarissa Felicia; Irawaty Hawari (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Sleep deprivation often occurs in those who live in social situations and lifestyles that support the occurrence of these conditions, for example in people who have a large workload or academic demands, including medical students. Moreover, the outbreak of the COVID-19 pandemic since 2020 has made various universities suspend face-to-face learning which has an impact on increasing assignment assignments. This study aims to determine the relationship between sleep quality and cognitive function in the Class of 2020-2021 Students of the Faculty of Medicine of Tarumanagara University during the COVID-19 pandemic. The research method used is an analytical observational study using a cross-sectional analysis design. Data was collected online through filling out the Pittsburgh Sleep Quality Index (PSQI) and Indonesian-language Montreal Cognitive Assessment (MoCA-INA) questionnaires by respondents during the period of December 2021 to May 2022. The results of the study obtained 249 respondents, of which 159 respondents had poor sleep quality (63.9%). Poor sleep quality was more commonly found in respondents in the age group of 20-22 years (67.2%), female gender (68.2%), group with history of routine drug consumption (88.2%), and history of consuming caffeinated drinks >2x/day (76.3%). There is a significant relationship between sleep quality and cognitive function in the Class of 2020-2021 Students of the Faculty of Medicine of Tarumanagara University during the COVID-19 pandemic (RR=6.575, p<0.0001) as a conclusion. It is hoped that the results of this study can serve as educational material and reference especially for university students so that they can apply good sleep hygiene practices to optimize sleep quality and cognitive function. Keywords: COVID-19, PSQI, MoCA-INA